Variasi konsentrasi kitosan dalam pembuatan bioplastik berbahan baku jerami nangka - Ok Ricky Jumatul Qadri; Farida Hanum Hamzah; Dewi Fortuna Ayu (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
One biopolymer that can enhance the characteristics of starch-based bioplastics is chitosan. This research intended to obtain the finest chitosan concentration on bioplastics made from jackfruit straw characteristics. This examine experimentally conducted employing a Completely Randomised Design (CRD) with four treatments and four replications to yield 16 experimental units. This study’s treatment included K1 (chitosan concentration: 2%), K2 (chitosan concentration: 4%), K3 (chitosan concentration: 6%), and K4 (chitosan concentration 8% ). The parameters examined in this research included water resistance, water vapor transmission rate, tensile strength, elongation, and biodegradability. The acquired data were statistically examined using analysis of variance (ANOVA). If the F count was more than or equal to the F table, the analysis would proceed with Duncan's New Multiple Range Test (DNMRT) at a significance level of 5%. The analysis of variance showed the addition of different concentrations of chitosan in the manufacture of bioplastic made from jackfruit straw had a significant effect on water resistance, water vapor transmission rate, tensile strength, elongation, and biodegradability. The best treatment in this study was the K1 with a chitosan concentration of 2%, which had swelling of 67,09%, water vapor transmission rate of 3,0379 g/m2/hour, and tensile strength of 14,68 MPa, elongation of 32,46%, and 8 days for complete degradation.